Determinação de cloreto por cromatografia de íons em petróleo extrapesado, coque e resíduo de vácuo após decomposição em sistema fechado por combustão iniciada por microondas - Pereira, Juliana Severo Fagundes (2007)
A method for chloride determination in heavy crude oil, petroleum coke and vacuum residue after microwave-induced combustion (MIC) in closed vessels is described. Samples (with exception of petroleum coke) were wrapped in polyethylene and placed on a quartz holder that was positioned inside to quartz vessels used in commercial system for sample digestion by microwave. Combustion takes place in the presence of oxygen under pressure (20 bar) using ammonium nitrate (50 ml of 6 mol l-1) as aid for ignition. The influence of absorbing solution (water, sodium carbonate, ammonium carbonate and hydrogen peroxide) on the recoveries for Cl and the necessity of an additional reflux step were evaluated. Water was selected as absorbing solution with 5 min reflux in view of the good agreement for certified reference material (coking coal) and to the suitability for further chloride determination using IC and inductively coupled plasma optical emission spectrometry (ICP OES). The recoveries for Cl were 99.4 ± 2.2% for heavy crude oil, 100.2 ± 1.9% for petroleum coke and 98.9 ± 2.2% for vacuum residue. Limits of detection (LOD) were 5 and 15 mg g-1 using IC and ICP OES, respectively. Additionally, wet digestion by microwave in closed vessels and water extraction in microwave also using closed vessels were evaluated for comparison of results. The residual carbon content was below 1% for the proposed procedure by MIC and higher than 10% for wet digestion in closed vessels. Another advantage is the possibility of using water or diluted alkaline solutions that is preferable for chloride and other halogen determination and its use can reduce the problems caused by loss of sensibility in IC due to matrix effects caused by strong acid or alkali solutions. With the proposed procedure it is possible to digest up to eight samples simultaneously using a sample mass up to 500 mg.